Mathematical modeling of angular displacements of the base machine of a twoconsole sprinkler unit - T. G. Gasanov; E. Z. Batmanov; M. R. Guseynov; M. T. Mutalibov (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The purpose of the study is to reveal the theoretical and practical aspects of mathematical modeling of the angular displacements of the base machine, which allows a deeper understanding of the principles of its operation and interaction with the environment.Method. With the help of a mathematical model, the issues of the interaction of the base machine with the road surface and the sprinkler farm were analyzed in three dynamic states of the unit in a plane perpendicular to the working movement of the base machine, the angular characteristics of the base machine turning in the transverse direction when hitting an obstacle at different speeds without taking into account the elastic-deforming ability of the soil.Result. The results of the study make it possible to evaluate the technical parameters of the angular displacements of the base machine on the magnitude of the impacts that disturb the unit.Conclusion. Allows you to correctly choose the basic principles of building an automatic control system for a sprinkler farm and roughly determine the main parameters of the equipment elements of the base machine of a two-console sprinkler unit.